Mental Health And Hope Among Patients Undergoing Hemodialysis - A, Nazneen.; Govind, K. (Journal of Neonatal Surgery, 2025)
Chronic disease of the kidney is an important cause of global mortality and morbidity.it has become a fast-expanding global problem related to health in all nations. End-stage renal disease is a complex, progressive, and debilitating illness that affects a patient’s quality of life, physical, and mental health, well-being, social functioning, and emotional health. Chronic kidney failure causes many limitations for patients. Despite the effectiveness of hemodialysis this method causes mental problems and frustration in patients. In the present study, the investigator aimed to assess the level of mental health and hope among patients undergoing hemodialysis. The researcher adopted a Descriptive Research design, and the data was collected through a questionnaire. Simple random sampling was used. A hundred samples were collected from the hospital and the dialysis center, Mental Health Inventory (MHI-38) by Veil and Ware (1983) and Herth Hope scale were used to collect the Data. There will be a positive relationship between Mental Health and Hope among patients undergoing hemodialysis.